Mapping of Flood-Prone Areas as a Flood Disaster Mitigation Effort in the Lambidaro Sub-Watershed, Palembang City - Muhammad Ardiansyah; Ngudiantoro N; Ari Siswanto (Program Pascasarjana Universitas Sriwijaya, 2023)
Palembang is a city that is frequently hit by floods, as the center of national activities which stimulates infrastructure development activities to support the economy and population growth, resulting in reduced urban green space and even the disappearance of the rivers that used to flow in most of Palembang City. Floods also occurred quite badly in the study area, namely the Lambidaro Sub-watershed, this study aims to identify the dominant factors that affect flooding and determine the area distribution based on the level of flooding vulnerability of study area. The methods used are Analytical Hierarchy Process analysis combined with Geographic Information System analysis using primary and secondary data from valid sources. Based on the results of the study, it was found that most of the study areas were in areas with a moderate level of flood prone with an area of 3146.50 hectares, then areas with a high level of flooding reached 1429.34 hectares, and finally, areas with a low level of flooding were only 347.65 hectares. The conclusion related to this research requires more attention from related stakeholders to areas that are included in the high flood-prone level, which mostly hit the Bukit Baru Village, Tanjung Barangan Street.